Transformative Impact of ICT on Education: Leveraging Technology and Communication to Enhance Teaching and Learning - Rakshak Bharti; Kasturi Pomal; Mariyam Ahmed; Chandra Bhooshan Singh (Feedback International Journal of Communication, 2024)
This research investigates the transformative role of Information and Communication Technology (ICT) in educational systems, with a specific focus on its impact on both teachers and students. As ICT becomes more integrated into classrooms, understanding its benefits and challenges is critical for enhancing the teaching and learning experience. The study employed a literature review approach, analyzing existing research on the use of ICT in schools, particularly focusing on its effects on student motivation, participation, achievement, and the attitudes of both students and teachers toward ICT integration. Various studies and case reports from diverse educational settings were examined to assess the overall impact. The findings indicate that ICT adoption in classrooms generally results in positive outcomes. Most studies reported a significant increase in students' motivation to learn, shifting away from traditional teaching methods. The research also highlighted improvements in students’ success rates, participation, computer skills, and overall academic achievement. However, some challenges were identified in ICT integration, particularly due to the advanced technological skills of younger generations, which, if not properly managed, could lead to misuse of technology for non-educational purposes. ICT has a transformative impact on education, enhancing student motivation, participation, and achievement. However, careful planning and oversight are required to ensure that technological advancements are used effectively in the classroom setting.